Merging the Matrix: Stratigraphy, Radiocarbon Dates, and Fire Regimens in the Ambato Valley (Catamarca, NW Argentina) - Marconetto, María Bernarda (2014)
This article compares radiocarbon dates and the stratigraphic matrix obtained from excavations at the Piedras Blancas archaeological site, Ambato Valley, NW Argentina. Analysis revealed inconsistencies between 14C dates and certain events that can be clearly identified in the stratigraphy of the site. This fact led first to recognize the importance of a detailed stratigraphic record to allow a point of control and comparison. Secondly, this article discusses for the present case, (a) the consistency shown by the dating performed on bone materials in relation to the stratigraphic matrix and (b) the inconsistencies identified in relation to the dating performed on charred plant material, although this type of material was chosen for collection and dating using all appropriate caution to prevent dating bias. Finally, the possibility is considered that the dated plant materials could be affected by the high microcharcoal concentrations observed in the valley's sediments as the result of fire regimes with a high frequency, which seem to have existed since at least about 4000 BP.